APA Handbook of Intellectual and Developmental Disabilities: Clinical and Educational Implications: Prevention, Intervention, A 2021
DOI: 10.1037/0000195-002
|View full text |Cite
|
Sign up to set email alerts
|

Applied behavior analysis and intellectual and developmental disabilities.

Abstract: Individuals with intellectual and developmental disabilities (IDD) present with deficits in intellectual functioning and support needs in adaptive behavior such as language, motor skills, social skills, and self-care skills (American Psychiatric Association, 2013). In addition, individuals with IDD are more likely than the general population to have physical disabilities, sensory impairments, seizures, and other health conditions such as infection, obesity, diabetes, and gastrointestinal disorders (Ouellette-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…Using Skinner's theory of operant condition, applied behavior analysis (ABA) analyzes and modi es human behaviors through the use of proactive and positive reinforcements. Applied behavior analysis allows school personnel to asses and treat challenging behaviors by introducing basic behavior principles outlined by Skinner's operant conditioning through systemic assessment and instructional procedures (Machalicek et al, 2021). Positive behavior modi cation in the classroom through applied behavior analysis has been widely studied, leading to its use for the early intervention for individuals with autism spectrum disorder (Machalicek et al, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Using Skinner's theory of operant condition, applied behavior analysis (ABA) analyzes and modi es human behaviors through the use of proactive and positive reinforcements. Applied behavior analysis allows school personnel to asses and treat challenging behaviors by introducing basic behavior principles outlined by Skinner's operant conditioning through systemic assessment and instructional procedures (Machalicek et al, 2021). Positive behavior modi cation in the classroom through applied behavior analysis has been widely studied, leading to its use for the early intervention for individuals with autism spectrum disorder (Machalicek et al, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Applied behavior analysis allows school personnel to asses and treat challenging behaviors by introducing basic behavior principles outlined by Skinner's operant conditioning through systemic assessment and instructional procedures (Machalicek et al, 2021). Positive behavior modi cation in the classroom through applied behavior analysis has been widely studied, leading to its use for the early intervention for individuals with autism spectrum disorder (Machalicek et al, 2021). Baer et al (1968) believed behaviors can be manipulated through positive reinforcements and a change in environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research has demonstrated the positive impact of ABA, and meta-analyses have shown medium to large effects of long-term, comprehensive ABA interventions on developmental outcomes for children with autism and other disabilities in early childhood (Eldevik et al, 2009; Feeley & Jones, 2006; Reichow & Wolery, 2009). Specifically for individuals with I/DD, ABA has been used in research to teach skills and behaviors targeting increased quality of life (e.g., Machalicek et al, 2021; Maffei-Almodovar, & Sturmey, 2018; Stauch, Plavnick, Sankar, & Gallagher, 2018).…”
Section: Need For Supports To Address Cbmentioning
confidence: 99%